Environmental Induction of White–Opaque Switching in Candida albicans - Ramírez-Zavala, Bernardo (Public Library of Science, 2008)

(untitled)
Candida albicans strains that are homozygous at the mating type locus (MTL a or MTLα) can spontaneously switch at a low frequency from the normal yeast cell morphology (white) to an elongated cell type (opaque), which is the mating-competent form of the fungus. The ability to switch reversibly between these two cell types also contributes to the pathogenicity of C. albicans, as white and opaque cells are differently adapted to specific host niches. We found that in strain WO-1, a strain in which genomic alterations have occurred, but not in other tested strains, switching from the white to the opaque phase can also be induced by environmental conditions. Transient incubation of white cells under anaerobic conditions programmed the cells to switch en masse to the opaque phase. The anaerobic induction of white–opaque switching was controlled by the transcription factor CZF1, which in heterozygous MTL a/α cells regulates filamentous growth under embedded, hypoxic conditions. Intriguingly, passage of white cells of strain WO-1 through the mouse intestine, a host niche in which the cells are likely to be exposed to anaerobic conditions, resulted in a strongly increased frequency of switching to the opaque phase. These results demonstrate that white–opaque switching is not only a spontaneous process but, in combination with genomic alterations, can also be induced by environmental signals, suggesting that switching and mating of C. albicans may occur with high efficiency in appropriate niches within its human host.